Ecological patterns strongly impact the biogeography of western Palaearctic longhorn beetles (Coleoptera: Cerambycoidea) - Vitali, Francesco; Schmitt, Thomas (Organisms diversity & evolution, 2017)
We aim to unravel the biogeographic structuring of western Palaearctic longhorn beetles with focus on the location of different refugia, barriers to dispersal and postglacial range expansions with their particular filters. The interaction of different ecological features with these structures is analysed. The western Palaearctic was divided into 95 geographic entities. We produced presence-only matrices for all 955 Cerambycoidea species autochthonous to this area and derived species richness distributions and extracted faunal regions and faunal elements by cluster analyses and principal component analyses. Similar analyses were performed for sub-families and ecological groups. Longhorn beetles show a strong biogeographic structuring in the western Palaearctic. Species numbers strongly decrease to the north and west. Less mobile species and root feeders mostly contribute to the fauna of the Mediterranean region, whilst mobile species are more widespread. Feeders on broad-leaved trees dominate in western Europe, whilst feeders on coniferous trees are most important in northern Europe. Our results support multiple refugia in the Mediterranean region and underline the importance of Provence, Crimea and Crete as such refugia. Crete even might be an area of old endemism. The Atlanto- and the Ponto-Mediterranean regions are more strongly structured than assumed in classical biogeography. Mediterranean assemblages are mostly composed of non-flying species, root feeders and species with small distributions not found outside their glacial refugia. Tree feeders left their glacial retreats with their host plants. These range dynamics result in biogeographic structures with several dispersal barriers and filters composed of mountains, sea straits and climatic conditions.